Female impersonators at a Christmas party. - Sahl, Ted (photographer):::Creator::::::::::::
Several members of the Casa de San Jose royal title holders at their annual Christmas party. Known individuals from left to right, Crescent Shalimar, Cheri La Salle, Doreen Tinney; and Lou Lou.